Reconfigurable Intelligent Surface‐Aided MIMO Secure Communication System With Finite‐Alphabet Inputs - Wu, Yingjie; Wang, Shilian; Luo, Junshan; Chen, Weiyu (Transactions on emerging telecommunications technologies, 2024)
ABSTRACT Existing research in the field of reconfigurable intelligent surface (RIS)‐aided physical layer security assumed Gaussian signal inputs, which is inapplicable to practical communication systems, where finite‐alphabet inputs are used. This paper considers an RIS‐aided secure multiple‐input multiple‐output wireless communication system with finite‐alphabet inputs, where artificial noise (AN) is invoked at the transmitter to enhance the secure performance. In order to maximize the secrecy rate (SR), the data precoder, the AN precoder, and RIS's reflection coefficients are jointly optimized subject to the constraints of the maximum transmit power and the finite resolution of the phase shifts of RIS. Particularly, due to the finite‐alphabet input, the exact expression of the SR involves multiple integrals and lacks a closed‐form expression. To tackle this, a closed‐form lower bound of the SR is derived as the objective function, which is theoretically proved to be equal to the SR in the high signal‐to‐noise ratio region. Numerical results show that the RIS can significantly improve the secure performance, and the maximum possible SR (due to the finite‐alphabet inputs) can be achieved by increasing the number of the RIS's elements or by increasing the transmit power, which shows the performance advantage of the proposed optimization algorithm. The existing works regarding reconfigurable intelligent surface (RIS)‐aided physical‐layer security considered the Gaussian input, which is however infeasible in practical systems. This paper proposed an algorithm that can fully utilize the advantages of the RIS and achieve the theoretical maximum secrecy rate for multiple‐input, multiple‐output transmission with finite‐alphabet inputs.